2014
DOI: 10.1111/bjd.13027
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridaemia with acitretin use: a proposal for its management in the context of overall cardiovascular risk

Abstract: meticulous physical examinations and taking a detailed history were essential in considering metastatic disease, which was confirmed by performing a histological examination. We have described an uncommon case of digital cutaneous metastasis, which could easily have been overlooked. We emphasize the importance of maintaining a high index of suspicion of neoplastic processes for lesions associated with cases of atypical clinical histories or morphologies. References1 Sur YJ, Kang YK, Bahk WJ et al. Metastatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In 2021, the US Food and Drug Administration required an update of the package insert for tofacitinib and other JAK inhibitors to carry a warning of risk for serious heart-related events, blood clots, cancer, and death based on data from a clinical safety trial in high-risk patients treated with tofacitinib compared with TNF blockers [ 69 ]. The conventional systemic psoriasis therapies methotrexate, cyclosporine, and acitretin are also associated with an increased risk of hypertriglyceridemia or increased lipid levels; however, the implications of these changes are not known [ 55 , 70 , 71 ]. In contrast, biologics used in psoriasis treatment have minimal effects on serum lipid profile.…”
Section: Safety Concerns For Psoriasis Treatment With Respect To Meta...mentioning
confidence: 99%
“…In 2021, the US Food and Drug Administration required an update of the package insert for tofacitinib and other JAK inhibitors to carry a warning of risk for serious heart-related events, blood clots, cancer, and death based on data from a clinical safety trial in high-risk patients treated with tofacitinib compared with TNF blockers [ 69 ]. The conventional systemic psoriasis therapies methotrexate, cyclosporine, and acitretin are also associated with an increased risk of hypertriglyceridemia or increased lipid levels; however, the implications of these changes are not known [ 55 , 70 , 71 ]. In contrast, biologics used in psoriasis treatment have minimal effects on serum lipid profile.…”
Section: Safety Concerns For Psoriasis Treatment With Respect To Meta...mentioning
confidence: 99%
“…In addition, acitretin also decreases the HDL fraction in 40% of patients 25 . High LDL/HDL ratio and hypertriglyceridemia are associated with cardiovascular risk 25,26 . Lipid abnormalities caused by acitretin typically reverses within 4–8 weeks after discontinuation 25 …”
Section: Discussionmentioning
confidence: 99%
“…25 High LDL/HDL ratio and hypertriglyceridemia are associated with cardiovascular risk. 25,26 Lipid abnormalities caused by acitretin typically reverses within 4-8 weeks after discontinuation. 25 Previous studies found that 28%-54% of GPP patients had scalp involvement.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%